Indoor air quality in new and renovated low‐income apartments with mechanical ventilation and natural gas cooking in California. (4th November 2020) - Zhao, Haoran; Chan, Wanyu R.; Cohn, Sebastian; Delp, William W.; Walker, Iain S.; Singer, Brett C.
Abstract: This paper presents pollutant concentrations and performance data for code‐required mechanical ventilation equipment in 23 low‐income apartments at 4 properties constructed or renovated 2013‐2017. All apartments had natural gas cooking burners. Occupants pledged to not use windows for ventilation during the study but several did. Measured airflows of range hoods and bathroom exhaust fans were lower than product specifications. Only eight apartments operationally met all ventilation code requirements. Pollutants measured over one week in each apartment included time‐resolved fine particulate matter (PM2.5 ), nitrogen dioxide (NO2 ), formaldehyde and carbon dioxide (CO2 ) and time‐integrated formaldehyde, NO2 and nitrogen oxides (NOX ). Compared to a recent study of California houses with code‐compliant ventilation, apartments were smaller, had fewer occupants, higher densities, and higher mechanical ventilation rates. Mean PM2.5, formaldehyde, NO2, and CO2 were 7.7 µg/m 3, 14.1, 18.8, and 741 ppm in apartments; these are 4% lower, 25% lower, 165% higher, and 18% higher compared to houses with similar cooking frequency. Four apartments had weekly PM2.5 above the California annual outdoor standard of 12 µg/m 3 and also discrete days above the World Health Organization 24‐hour guideline of 25 µg/m 3 . Two apartments had weekly NO2 above the California annual outdoor standard of 30 ppb.